LA INVESTIGACIÓN-ACCIÓN COMO HERRAMIENTA PARA TRANSFORMAR LAS PRÁCTICAS DOCENTES EN LA ENSEÑANZA DEL INGLÉS (De la Crítica, 2025)
The purpose of this essay was to analyze how action-research can be used to improve and transform teaching practices in the instruction of English as a foreign language, promoting educational quality and meaningful learning among students. This essay was carried out through the review of documents related to action research in the teaching of the English language. The findings of the study affirm that action-research is positioned as a strategic and transformative tool in English teaching, enabling teachers to reflect on their practices, identify areas for improvement, and design solutions tailored to their students' needs.